2018
DOI: 10.1002/mbo3.523
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic microbial profiling in water samples from a Brazilian Amazonian reservoir

Abstract: Our comprehension of the dynamics and diversity of freshwater planktonic bacterial communities is far from complete concerning the Brazilian Amazonian region. Therefore, reference studies are urgently needed. We mapped bacterial communities present in the planktonic communities of a freshwater artificial reservoir located in the western Amazonian basin. Two samples were obtained from rainy and dry seasons, the periods during which water quality and plankton diversity undergo the most significant changes. Hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
3
1
0
Order By: Relevance
“…Taxonomical composition revealed that the Proteobacteria phyla were most common, followed by Cyanobacteria and Actinobacteria. These results are consistent with other Brazilian studies that describe the microbial communities in the Amazon basin (22)(23)(24) and Tocantins River (25) but somewhat different from those previously described for reservoirs in China. For instance, Qu J et al used the 16S rDNA Illumina approach and showed that Firmicutes, Proteobacteria, Cyanobacteria, and Bacteroidetes were the dominant bacterial phyla in the Miyun Reservoir, which is considered the largest man-made reservoir in North China.…”
Section: Discussionsupporting
confidence: 91%
“…Taxonomical composition revealed that the Proteobacteria phyla were most common, followed by Cyanobacteria and Actinobacteria. These results are consistent with other Brazilian studies that describe the microbial communities in the Amazon basin (22)(23)(24) and Tocantins River (25) but somewhat different from those previously described for reservoirs in China. For instance, Qu J et al used the 16S rDNA Illumina approach and showed that Firmicutes, Proteobacteria, Cyanobacteria, and Bacteroidetes were the dominant bacterial phyla in the Miyun Reservoir, which is considered the largest man-made reservoir in North China.…”
Section: Discussionsupporting
confidence: 91%
“…Taxonomical composition revealed that the Proteobacteria phyla were most common, followed by Cyanobacteria and Actinobacteria. These results are consistent with other Brazilian studies that describe the microbial communities in the Amazon basin [22][23][24] and Tocantins River [25] but somewhat different from those previously described for reservoirs in China. For instance, Qu J et al used the 16S rDNA Illumina approach and showed that Firmicutes, Proteobacteria, Cyanobacteria, and Bacteroidetes were the dominant bacterial phyla in the Miyun Reservoir, which is considered the largest man-made reservoir in North China.…”
Section: Discussionsupporting
confidence: 91%
“…The taxonomical composition revealed that the Cyanobacteria phylum was the most abundant in the community, followed by Proteobacteria and Actinobacteria . These results are consistent with other Brazilian studies that describe bacterial communities in the Amazon basin [ 57 , 58 , 59 ] and Tocantins River [ 60 ], but are somewhat different from those previously described for reservoirs in China. For instance, Qu J et al [ 56 ] used the 16S rDNA Illumina approach to show that Firmicutes , Proteobacteria , Cyanobacteria , and Bacteroidetes were the dominant bacterial phyla in the Miyun Reservoir, which is considered the largest man-made reservoir in North China.…”
Section: Discussionsupporting
confidence: 89%